Interpreting Deixis and Referential Meaning in Harris J’s ‘Promise’ - Al Bisri, Muhammad Burhanudin; Aisyah, Siti; Hastuti, Umi Nur (Journal of English Language and Education, 2025)
This study analyzes the use of deixis in the lyrics of Harris J’s song “Promise”, focusing on deixis categories, their frequency, and their referential meanings. The objectives are to identify the types of deixis present in the lyrics, determine the most dominant type, and interpret the referential meanings of each deictic expression. Grounded in George Yule’s (2006) theory of deixis and employing a descriptive qualitative method, data were collected by listening to the song and closely examining the lyrics. The findings reveal three types of deixis: person deixis, temporal deixis, and spatial deixis. Person deixis was the most frequently used, with 60 instances (68.97%), followed by spatial deixis (13 instances, 14.94%) and temporal deixis (11 instances, 12.64%). The referents of person deixis typically include the singer and the listener, underscoring the emotional and personal tone of the lyrics. Temporal deixis points to moments of memory and promise, while spatial deixis reflects emotional proximity and movement. Overall, deixis in the song enriches its expressive quality, strengthening the listener’s emotional connection with the narrative.